Study on the characteristics of motorcycle taxis in Metro Manila - Mangco, Raniel Abraham A.; Montiveros, Justy Lucille T.
Motorcycle taxis have emerged as an alternative mode of transportation in the Philippines during the nineties but until now, there are still no policies, local or national, that regulate their operation. The purpose of this study is to identify the usage and operational characteristics of conventional motorcycle taxis in Metro Manila and to determine the service perception of the users and non-users to come up with policy recommendations regarding their operations. Three different questionnaires were produced: one for the drivers, one for the users and the other one for the non-users. For the drivers, the questionnaire consisted of questions about their basic information, terminal characteristics, operational characteristics, fare and route characteristics, and safety and legal concerns. The users were asked about their basic information, fare and route characteristics, perceptions of motorcycle taxi service and of motorcycle taxi drivers, and safety and legal concerns. And lastly, the non-users were asked about their basic information, perceptions of motorcycle taxi service, and safety and legal concerns. After performing field interview, 78 drivers, 96 users, and 121 non-users were interviewed in eight terminals namely Guadalupe, Sucat, Bicutan, Napindan, Balara, Gate 3 Bonifacio, Villamor, and Merville. However, the study is focused only in four terminals: Guadalupe, Bicutan, Sucat and Napindan as these are the locations with the highest number of interviewees. Based from the data gathered, 43.8% (42 out of 96) of the total users ride a motorcycle taxi every day and 84.4% (81 out of 96) use the service at least once a week. In Guadalupe and Napindan, 87% (13 out of 15) and 66% (40 out of 60) of the users, respectively, are private company employees. In Bicutan, only 46% (6 out of 13) of the users are private company employees and 39% (5 out of 13) are students. It is also determined that 93.3% (14 out of 15) of the users in Guadalupe use the service to go to work compared to 75% (45 out of 60) of the users in Napindan and only 30.8% (4 out of 13) of the users in Bicutan, where 38.5%(5 out of 13) of its users use the service to go to school. The drivers in both Guadalupe and Napindan are required to pay organization and terminal fees; however, in Sucat, no fees are required even though they also have an organization. The calculated average monthly income of the drivers in Guadalupe, Napindan and Sucat are P 16,957.89, P12,280.00 and P6,070.00, respectively. The drivers in Guadalupe and Napindan Actually Earn more than the minimum wage. Additionally, the drivers in Guadalupe earn the highest even though the drivers in Napindan makes the most number of trips per day. As for the legal issues, the users are actually more aware that motorcycle taxis are illegal. Only 71.9% (87 out of 121)of the non-users knew that they are illegal compared to 90.6% (87 out of 96) of the users who know yet continue to use the service. Also, 68.6% (83 out of 121) of the non-users considers riding motorcycle taxis once they are regulated and this increases to 76% (92 out of 121) if Uber/Grab offer the service. Motorcycle taxis should be regulated because there is a demand for this service and it provides decent job for the drivers. However, the safety of the passengers should be prioritized when coming up with regulations since 6.3% (6 out of 96) of the users and 17.9% (14 out of 78) of the drivers have been involved in accident while using motorcycle taxis.